BACILLUS DIVERSITY ANALYSIS IN CITRUS RHIZOSPHERE SOIL (Journal of Plant Disease Sciences, 2017)
The present investigation was related to find out the diversity in Bacillus citrus rhizosphere. The research survey entitled " Diversity Analysis in Bacillus Citrus Rhizosphere Soil" was carried out at Hingna tahsil of Nagpur district in the month of September, 2014. Soil contains bacterial count ranged from 36×10 to 3 53×10 cfu g in low yielding soils while 45×10 to 108×10 cfu g in optimum 3 -1 3 3 -1 yielding and 86×10 to 132×10 cfu g in high yielding citrus rhizosphere, 3 3 -1 Bacillus subtilis Bacillus polymyxa count ranged from 8×10 to 33×10 cfu g , ranged from 3 3 -1 2×10 to 12×10 cfu g . ranged from 4×10 to 23×10 cfu g . 3 3 -1 3 3 -1 Bacillus licheniformis Bacillus mycoides Bacillus pumilus ranged 8×10 to 39×10 cfu g . ranged from 3 3 -1 1×10 to 11×10 cfu g and count ranged 6×10 to 14×10 cfu g . 3 3 -1 3 3 -1 Bacillus cereus
Keywords: Bacillus, diversity, citrus , rhizosphere